University-Local Industry Linkages: The Case of Tohoku University in the Sendai-Area of Japan - Jiang, Juan; Harayama, Yuko; Abe, Shiro (World Bank, Washington, DC, 2012)
This paper focuses on Tohoku University in Sendai in the nonmetropolitan area of Japan. Both a long historical and comparative perspective and a spacial perspective are essential to discuss the relevance of university-local industry linkages to local regional economic development. The conjunction of these linkages and economic development has been affected by two evolutionary processes: institutional configurations and territorial dynamics in the national innovation system. In addition, university-local industry linkages have been complicated by top-down regionalization and bottom-up regionalism.